2015
DOI: 10.17511/ijmrr.2015.i6.114
|View full text |Cite
|
Sign up to set email alerts
|

Twin Pregnancy discordordant for Downs syndrome: Case Report

Abstract: The work presented is a clinical and genetical trial of a couple with a reproductive failure and a family history of chromosomal abnormalities. The most reliable and accurate methods used for antenatal diagnosis of Down syndrome fetuses are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Considering these observations as well as the application of MSS (AFP, hCG and uE3) in predicting risk for Down syndrome and other congenital anomalies, we started to use in the Clinic of Obstetrics and Gynecology of the Prof. Dr. Panait Sarbu Hospital in Bucharest the serial ultrasound test associated with dosages of AFP, hCG and uE3 [28]. When maternal serum screening is performed for the usual clinical indication , abnormal analyte results can be utilized for the identification of pregnancies at risk and to direct their clinical management [25].…”
Section: Resultsmentioning
confidence: 99%
“…Considering these observations as well as the application of MSS (AFP, hCG and uE3) in predicting risk for Down syndrome and other congenital anomalies, we started to use in the Clinic of Obstetrics and Gynecology of the Prof. Dr. Panait Sarbu Hospital in Bucharest the serial ultrasound test associated with dosages of AFP, hCG and uE3 [28]. When maternal serum screening is performed for the usual clinical indication , abnormal analyte results can be utilized for the identification of pregnancies at risk and to direct their clinical management [25].…”
Section: Resultsmentioning
confidence: 99%
“…Fetal SCT is usually reported in singleton pregnancy.Few literatures reported STC in one twin in twin pregnancy. We performed an extensive search and make a literature review in English and Chinese and found fewer than 9 cases of SCT in one twin had been reported [ 10 , 17 – 22 ]. Detailed information are showed in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The risk of giving birth to a child with Down syndrome increases with the mother's age [28]. Thus, the risk of mothers under 29 is 1 / 3,000 births, at 30 it increases sharply to 1/700, and at 45 the risk is almost unacceptable, being 1/40 of births [28,[31][32][33].…”
Section: Mthfr C677t Gene Mutation and Maternal Risk Of Down Syndromementioning
confidence: 99%